READING LITERACIES THROUGH EVIETA-BASED LEARNING MATERIAL: STUDENTS’ PERCEPTIONS (Study Case Taken from Vocational School – IPB University) - Barus, Irma Rasita Gloria; Simanjuntak, Marudut Bernadtua; Resmayasari, Ira (Study Program of English Literature, 2021)
Communities with high literacy rates usually have low crime rates and high intelligence. This is precisely the responsibility of universities and schools in increasing reading interest and literacy skills in a country. From this context, it is hoped that the educational community will really apply it, especially in juxtaposing it with online learning and several applications. The purpose of this study was to collect information about the preferences of critical vocational students in their reading interests and reading skills. It is very useful to foster interest in reading and online learning to increase cultural values ​​and social literacy. The reading literacy development model used is the Plomp model: preliminary research, prototyping, and evaluation. The Evieta application, which is online learning belonging to the Vocational School of IPB University, is expected to fulfill these goals. Educators are expected to use related applications in their learning and lead reading and writing movements in schools. The results of the validation of teaching materials show that the Evieta IPB application is important and can be tested.